Efeito do treinamento resistido e reposição de hormônio sobre o transportador de glicose hepático (GLUT2) de ratas ovariectomizadas - Tomaz, Luciane Magri (2016)
Oestrogens withdrawal in rats, through ovariectomy (Ovx), has been repeatedly associated with disturbances in lipid metabolism. Among them, liver fat accumulation is well substantiated. On the other hand, there is few information on how liver fat in Ovx rats may affect glucose metabolism in liver. The purpose of the study was to investigate the effects of Ovx and 12 weeks resistance training (RT) program on gene expression of GLUT2 the main glucose transporter in liver and on PPARy a transcription factor known to target GLUT2 gene expression. RT in rat is an exercise training model that has received little attention but that has been shown to result in metabolic adaptations in Ovx rats as well as in post-menopausal women. Holstman rats were divided into 5 groups: Sham-sedentary (Sed), Sham-resistance trained (RT), Ovx-Sed, Ovx-RT, and Ovx-Sed with hormone replacement (E2). The RT protocol consisted of resistance training sessions held every 72 h for 12 weeks, during which session the animals performed 4 to 9 vertical climbs (1.1 m) with progressive weights (up to 30 g) tied to the tail at 2 min intervals. In addition to liver fat, GLUT2 protein levels and PPARy transcripts were all increased (P < 0.05) in Ovx compared to Sham-Sed animals, suggesting an increase hepatic glucose uptake under oestrogens withdrawal. Resistance training as well as oestrogens replacement in Ovx rats decreased liver fat accumulation as well as GLUT2 and PPARy gene expression to the level of Sham-Sed group. The present results suggest that liver fat accumulation in Ovx rats is accompanied by an increased glucose uptake thus providing substrate for an increased de novo lipogenesis. RT appears to be an appropriate exercise model to circumvent these effects.